Morphological Array of Cardiac and Coronary Artery Diseases in Cases of Sudden Death: An Autopsy-Based Histopathological Study in Rural Setup - Subathra, K; Gokula Pandiasankar, M R; Kavitha , D; Shobana , R (Journal of Indian Academy of Forensic Medicine, 2023)
Cardiovascular diseases are the foremost cause of sudden death in adults. The primary objective of this study is to estimate the prevalence of various cardiac and coronary artery diseases in sudden unexpected death cases in rural setup. Estimation of age and sex-wise frequency of coronary atherosclerotic disease (CAD), and grading of CAD by applying the Modified American Heart Association (AHA) classification are secondary objectives. In this three years prospective cross-sectional study, heart specimens were studied from 136 persons whose death was sudden and unexpected. Gross dissection and histopathological examination of coronary arteries and heart were done. Diagnoses were based on both gross and microscopic findings. CAD with or without other diseases was the most frequent pathology (n-100, 73.5%). Left ventricular hypertrophy in 45 cases (33.09%), myocardial infarction in 30 cases (22.06%), valvular abnormalities in three cases (2.2%), infective endocarditis in two cases (1.47%), aortic dissection in one case (0.74%), right ventricular hypertrophy in one case (0.74%) and cardiac myocyte atrophy in one case (0.74%) were observed. Male-female ratio of CAD was 8.09:1. Advanced CADs (type IV, V, VI) were found in 94 (94%) cases. In males, the maximum number of advanced CAD was observed in the fifth decade (n- 27, 31.76%) and in females in the seventh decade (n- 4, 44.44%). This study reveals the increasing trend of CAD in rural populations. This study adds rare entities like young-age aortic dissection and cardiac myocyte atrophy to the existing literature and emphasises the importance of autopsy in sudden death cases.